Study on the Quality of Walkable Streets in Dhapakhel Neighborhood, Lalitpur District, Nepal - Bhatt, Ganga Sagar; Bhatta, Kishan Datta; Joshi, Janardan (Journal of Engineering Technology and Planning, 2025)
Streets are vital public spaces that shape urban life and mobility, with sidewalks serving as essential yet often neglected pedestrian zones. Despite their importance, pedestrian facilities in many Nepali cities remain poorly designed and undervalued. This study examines the condition of streets in Dhapakhel, Lalitpur, emphasizing the need for pedestrian-friendly urban environments. Using field observation, spatial analysis, photographic documentation, and user surveys, the research evaluates accessibility, safety, and comfort for pedestrians. Findings reveal inadequate pedestrian infrastructure, obstructed walkways, and lack of supportive amenities. The study recommends adopting human-centered street design and implementing effective policies to create safer, more inclusive, and pedestrian-friendly urban environments.